POTENSI DAN EFEKTIVITAS PEMUNGUTAN RETRIBUSI RSUD Dr. AGOESDJAM KETAPANG - B61110063, JAMALUDIN (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This study entitled Potential and Effectiveness of retribution collecting in RSUD Dr. Agoesdjam Ketapang which aims to identify and analyze the potential retribution of RSUD Dr . Agoesdjam and also to investigate and analyze the effectiveness of the retribution collecting in RSUD Dr. Agoesdjam . This study uses secondary data , from 2008 to 2012 that were obtained from the Regional Revenue Office of Ketapang and RSUD Dr. Agoesdjam Ketapang . The method of this study is descriptive. To analyze the data in this study, the writer used an analysis tools, such as: the retribution potential, the retribution capacity and the retribution-effort ratio. The results of the study showed that the potential room of RSUD Dr. Agoesdjam is fluctuating and lower realization of the targets set, the efforts retribution that undertaken by RSUD Dr. Agoesdjam known from 2008 to 2012 has been effective although in 2009 and in 2010 was still effective enough that sometimes due to the policy of the leadership on the use of inpatient rooms where patients should be staying at class II for class II employees being treated in the VIP room so that there is difference of payment to be paid, and for hospitalized patients in class III are borne by local governments with not complete files that have been prepared form, while for the retribution capacity RSUD Dr. Agoesdjam very effective in average from 2008 to 2012, but in 2010 the retribution capacity of RSUD Dr. Agoesdjam is not effective, because of government policy which states that the funds claims Jamkesda that paid by local governments should not be included as contribution income RSUD Dr. Agoesdjam resulting that the retribution capacity to be non effective and also caused by the very high increase in the target. Keyword : retribution potential, retribution capacity and retribution-effort ratio